The Ernest Gellner Nationalism Lecture: The Soviet Union, self‐determination, and the creation of the postwar human rights system. Issue 2 (6th February 2020) - Weitz, Eric D
Abstract: The USSR played a key role in the establishment of the post‐World War II human rights system despite its repressive and even murderous domestic record. It forged an alliance with the countries of the Global South in support of decolonization, self‐determination, and social and economic rights, policies opposed by liberal states like the United States, Great Britain, and France. These positions were deeply rooted in the socialist tradition. Moreover, when a human rights movement emerged in the mid‐1960s, its members—in its origins overwhelmingly from the intelligentsia—called not for the overthrow of the Soviet Union but for the fulfilment of Soviet law. The language of rights, proclaimed with such flourish in the 1936 constitution and its successor in 1977, served as the weapon hurled by dissidents as they called on the Soviet government to respect freedom of speech and assembly, and national rights, including the right to emigrate. In turn, the international human rights movement developed from the 1960s to the 1990s largely through support for the Soviet dissident movement, Amnesty International, and Human Rights Watch prime examples. The Soviet experience is critical to any global history of human rights.